Genesis 1:1-3 in Selected Akan Mother-tongues: A Grammatico-syntactic Analysis - Alfred Korankye; Emmanuel Twumasi-Ankrah; Isaac Boaheng (E-Journal of Humanities, Arts and Social Sciences)
The translation of the Bible message from the original language to a receptor language has been challenging due to the lack of equivalent words in the receptor language to convey the exact meaning of the original language. This can sometimes distort the original meaning and create ambiguity in the receptor community. In some Akan dialects such as Asante-Twi, Akuapim-Twi, and Bono-Twi, the translation of Genesis 1:1-3 presents recognizable translational challenges when compared with the Masoretic Text. For instance, all the selected Akan dialects translated the Hebrew word bereshit, “In the beginning,” as independent in relation to other parts of the first sentence. However, this paper argued that rendering bereshit, with no indication of the temporal dependent relationship function of the clause within the sentence thus without any circumstantial sense, limits the meaning of the sentence and is inconsistent with the source text. Employing grammatical and syntactical analysis, the paper identified some translational inconsistencies in the selected Akan mother-tongue Bibles and accordingly proposed alternative renderings for readers.